EFFECT OF USING SODIUM BICARBONATE AND MIXTURE OF VITAMIN E AND SELENIUM IN PRODUCTION PERFORMANCE OF AWASSI EWES - & et al., Tayeb (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was conducted by using18 Awassiewes , 2-4 years aged, with average body weight 61.56 kg. The ewes were randomly divided into three groups, six ewes in each group. All ewes received 1.5 kg/ dry matter from the same basal diet consist mainly of barley, wheat bran, soybean meal and wheat straw . The first group was fed on basal ration only ( T1 ) ,while 45g /ewe /day sodium bicarbonate was supplemented to the feed of the second (T2)group and third (T3) group was supplemented with 45g sodium bicarbonate plus 0.5g mixture of Vitamin E and selenium /ewe/day. Results showed that the treatments hadsignificant increase( P < 0.05 ) on milk production of T3(739 g/d) than T1,T2(571and 599 g/d)respectively. No effect on average body weight, lactose, fat and protein percentage in milk. Rumen liquor pH, ammonia and total count of rumen bacteria and protozoa before feeding was not affected, while after 2hr of feeding, pH value of rumen liquor was increased (P < 0.05) in T2 6.65 as compared with T1 5.62 and T3 6.13. Ammonia and microorganism concentration in rumen liquor and blood parameters were not affected by experimental treatments.